Strange Plantings: Robert Kroetsch's Seed Catalogue - Campbell, Wanda (Studies in Canadian Literature)

(untitled) (None, 1996)
While much has been made of Robert Kroetsch's use in his poetry of an archaeological model derived from sources including Heidegger, Williams, Olson, and Foucault, in his long poem Seed Catalogue, the poet makes use of a horticultural model. A close reading of Seed Catalogue reveals the poem's central question -- "How do do you grow a poet?" -- serving as a guide to Kroetsch's workings through his own genesis as a prairie writer in a literary landscape dominated by fiction. Seed Catalogue's hybrid form is evidence of the beginnings (or seeds) of, the numerous models for, and the various methodologies employed in the service of such development.